Supervisi Edukatif Kolaboratif untuk Meningkatkan Kinerja Guru Merencanakan Kegiatan Pembelajaran di SDN 01/X Rantau Indah Semester Ganjil Tahun Ajaran 2021/2022 - Rosidah Rosidah (Departement of Mathematics Education, 2022)
This study aims to obtain information and discuss collaborative educational supervision to improve teacher performance in planning learning activities at SDN 01/X Rantau Indah in the odd semester of the 2021/2022 academic year. This type of research is school action research which consists of two cycles with each cycle consisting of four stages, namely planning, implementation, observation and reflection. This research was conducted at SDN 01/X Rantau Indah in the odd semester of the 2021/2022 academic year with the subject of teacher research at SDN 01/X Rantau Indah totaling 7 people consisting of 6 class teachers and 1 PAI teacher. Data collection techniques using observation, field notes, interviews, and documentation. Data were analyzed using percentages and data reduction. The results showed that through collaborative educative supervision could improve teacher performance in classroom learning at SDN 01/X Rantau Indah